2022
DOI: 10.3390/risks10030056
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 Pandemic and Overconfidence Bias: The Case of Cyclical and Defensive Sectors

Abstract: This research paper analyses the impact of COVID-19 to investigate the overconfidence bias in 12 cyclical and defensive sectors in pre- and during COVID-19 periods using daily data from 1 January 2015 to 31 December 2020. The results of VAR show that in the pre COVID-19 phase overconfidence bias is more prevalent in all the cyclical sectors; in particular, MEDIA, METAL and REALTY have highly significant coefficients . In the defensive sectors, the VAR outcomes are not as strong as we expected, except for SERVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…The connection between these two schools of thought is referred to as a "traditionalist" relationship in the negative sense and a "revisionist" relationship in the positive sense. According to this point of view, there will be a positive association between environmental performance and financial success up to the level of environmental performance at which economic advantages will be at their highest level (Ayesha et al, 2022;Azam et al, 2022;Gregory, 2022).…”
Section: Environmental Disclosure and Firm's Performancementioning
confidence: 99%
“…The connection between these two schools of thought is referred to as a "traditionalist" relationship in the negative sense and a "revisionist" relationship in the positive sense. According to this point of view, there will be a positive association between environmental performance and financial success up to the level of environmental performance at which economic advantages will be at their highest level (Ayesha et al, 2022;Azam et al, 2022;Gregory, 2022).…”
Section: Environmental Disclosure and Firm's Performancementioning
confidence: 99%
“…It is worthwhile to utilize when it is more accurate than projections based on mechanically adding up the expenses of shutting down various sectors of the economy. Furthermore, as seen by widespread lockdowns and restrictions to prevent new infections, the outbreak has had a significant effect on the economic slowdown, unemployment (Uddin and Alam, 2021;Azam et al, 2022), The motivation of this study is to seek the impact of uncertainties and emittances on household consumption with the inclusion and exclusion of covid effects in empirical estimation. The study has taken into account three panels of data which are sub-grouped according to income level that is lower-income countries (LIC), Lower-middle income countries (LMIC) and Upper-Middle-Income Countries (UMIC), respectively, for the period 1996-2020.…”
Section: Introductionmentioning
confidence: 99%
“…However, during the COVID-19 phase overconfidence bias was more pronounced in IT and Pharma sectors along with metal, media, and realty sector. The study also found out that overconfidence bias has no influence in the energy sector (Azam, Hashmi, Hawaldar, Alam & Baig, 2022). Focusing on the determinants of overconfidence bias it was found that all the cognitive biases influence overconfidence bias and illusion of control is the most influencing variable (Ul Abdin, Qureshi, Iqbal & Sultana, 2022).…”
mentioning
confidence: 85%